Hybrid deep-learning model to recognise emotional responses of users towards architectural design alternatives. Issue 5 (3rd September 2019) - Chang, Sunwoo; Jun, Hanjong
ABSTRACT: In architectural planning and initial designing process, it is critical for architects to recognise users' emotional responses toward design alternatives. Since Building Information Modelling and related technologies focuses on physical elements of the building, a model which suggests decision-makers' subjective affection is strongly required. In this regard, this paper proposes an electroencephalography (EEG)-based hybrid deep-learning model to recognise the emotional responses of users towards given architectural design. The hybrid model consists of generative adversarial networks (GANs) for EEG data augmentation and an EEG-based deep-learning classification model for EEG classification. In the field of architecture, a previous study has developed an EEG-based deep-learning classification model that can recognise the emotional responses of subjects towards design alternatives. This approach seems to suggest a possible method of evaluating design alternatives in a quantitative manner. However, because of the limitations of EEG data, it is difficult to train the model, which leads to the limited utilisation of the model. In this regard, this study constructs GANs, which consists of a generator and discriminator, for EEG data augmentation. The proposed hybrid model may provide a method of developing supportive and evaluative environments in planning, design, and post-occupancy evaluation for decision-makers.